2021
DOI: 10.3390/medicina57090961
|View full text |Cite
|
Sign up to set email alerts
|

Transition of Living Arrangement and Cognitive Impairment Status among Chinese Older Adults: Are They Associated?

Abstract: Background and Objectives: Living arrangement is a crucial factor for older adults’ health. It is even more critical for Chinese older adults due to the tradition of filial piety. With the aging of China’s population, the prevalence of cognitive impairment among older adults has increased. This study examines the association between living arrangement transition and cognitive function among Chinese older adults. Materials and Methods: Using three waves of the Chinese Longitudinal Healthy Longevity Survey (CLHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Living alone was not associated with poorer cognitive function at baseline and follow-up [ 38 ]. In line with this, older adults who transitioned to living alone (due to death of or divorce from spouse) had a lower risk of cognitive impairment, compared to those who continued to live with others [ 59 ]. However, men who lived alone in old age were twice as likely to experience cognitive decline compared to those married or living with someone [ 74 ], (see detail on gender influence below).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Living alone was not associated with poorer cognitive function at baseline and follow-up [ 38 ]. In line with this, older adults who transitioned to living alone (due to death of or divorce from spouse) had a lower risk of cognitive impairment, compared to those who continued to live with others [ 59 ]. However, men who lived alone in old age were twice as likely to experience cognitive decline compared to those married or living with someone [ 74 ], (see detail on gender influence below).…”
Section: Resultsmentioning
confidence: 99%
“…Living arrangements were found to be one of the factors more strongly associated with cognitive ability in older people [ 45 ]. Older people living in multigenerational family household often had poorer cognitive function than those living with a spouse or non-relatives [ 59 ]. Data collected in Taiwan found that social participation outside the family may have a larger effect on cognition than the social contracts within the family [ 44 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both patients were widows and lived alone. While the death of a husband is clearly a stressful factor, there are paradoxical studies demonstrating the benefits of living alone for the cognitive function of older adults ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is related to multiple factors, including objective and subjective indicators, respectively (17). Although objective functional health is the main predictor of perceived health, empirical results on the associations between functional health and subjective health are often inconsistent, ranging from low and non-significant associations to highly significant associations (16,(18)(19)(20)(21)(22). Part of this heterogeneity may be based on the assessment of the expanded function in functional health, mainly leisure activities (23).…”
Section: Introductionmentioning
confidence: 99%